Pneumococcal Colonization and the Nasopharyngeal Microbiota of Children in Botswana. Issue 11 (November 2018) - Kelly, Matthew S.; Surette, Michael G.; Smieja, Marek; Rossi, Laura; Luinstra, Kathy; Steenhoff, Andrew P.; Goldfarb, David M.; Pernica, Jeffrey M.; Arscott-Mills, Tonya; Boiditswe, Sefelani; Mazhani, Tiny; Rawls, John F.; et al.
Abstract : Background: Nasopharyngeal colonization precedes infections caused by Streptococcus pneumoniae . A more detailed understanding of interactions between S. pneumoniae and the nasopharyngeal microbiota of children could inform strategies to prevent pneumococcal infections. Methods: We collected nasopharyngeal swabs from children 1 to 23 months of age in Botswana between August 2012 and June 2016. We tested samples for S. pneumoniae and common respiratory viruses using polymerase chain reaction. We sequenced the V3 region of the bacterial 16S ribosomal RNA gene and used random forest models to identify clinical variables and bacterial genera that were associated with pneumococcal colonization. Results: Mean age of the 170 children included in this study was 8.3 months. Ninety-six (56%) children were colonized with S. pneumoniae . Pneumococcal colonization was associated with older age ( P = 0.0001), a lack of electricity in the home ( P = 0.02) and household use of wood as a cooking fuel ( P = 0.002). Upper respiratory symptoms were more frequent in children with S. pneumoniae colonization (60% vs. 32%; P = 0.001). Adjusting for age, nasopharyngeal microbiota composition differed in colonized and noncolonized children ( P = 0.001). S. pneumoniae colonization was associated with a higher relative abundance of Moraxell a ( P = 0.001) and lower relative abundances of Corynebacterium ( P = 0.001) and Staphylococcus ( P = 0.03). A decision tree model containing the relative abundances of bacterial genera had 81% sensitivity and 85% specificity for the determination of S. pneumoniae colonization status. Conclusions: S. pneumoniae colonization is associated with characteristic alterations of the nasopharyngeal microbiota of children. Prospective studies should determine if nasopharyngeal microbial composition alters the risk of pneumococcal colonization and thus could be modified as a novel pneumonia prevention strategy. Abstract : Supplemental Digital Content is available in the text.